Review of community pharmacy services: what is being performed, and where are the opportunities for improvement? - Melton BL; Lai Z (Dove Medical Press, 2017)
Brittany L Melton, Zoe Lai Department of Pharmacy Practice, University of Kansas, Lawrence, KS, USA Objective: The aim of this review was to assess pharmacist and pharmacy services being provided and identify opportunities to improve patient satisfaction.Methods: Studies published between January 2006 and July 2016 examining patient satisfaction with pharmacy and pharmacist services, which were written in English, were identified in PubMed. Studies were excluded if they only looked at pharmacy student-provided services.Key findings: A total of 50 studies were ultimately included in the review. Of these studies, 28 examined services traditionally provided by community pharmacists such as dispensing and counseling, while 16 examined a new in-person service being offered by a pharmacy, and the remaining six involved a new technology-assisted service. While study findings were generally positive for patient satisfaction of pharmacy services, several opportunities were identified for pharmacies to improve.Conclusion: Overall, patient satisfaction is high across pharmacy services; however, this satisfaction is related to prior patient exposure to services and their level of expectation. Pharmacists have multiple opportunities to improve the services they provide, and there are additional services pharmacists may consider offering to expand their role within the health care system. Keywords: pharmacy, services, community, patient satisfaction